2023
DOI: 10.12688/f1000research.128912.1
|View full text |Cite
|
Sign up to set email alerts
|

The refusal of COVID-19 vaccination and its associated factors: a systematic review

Abstract: Background: To date, more than 10% of the global population is unvaccinated against the coronavirus disease 2019 (COVID-19), and the reasons why this population is not vaccinated are not well identified. Objectives: We investigated the prevalence of COVID-19 vaccine refusal and to assess the factors associated with COVID-19 vaccine refusal. Methods: A meta-analysis was conducted during August to November 2022 (PROSPERO: CRD42022384562). We searched articles investigating the refusal of COVID-19 vaccination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…A systematic review by Tamara et al investigated the refusal of the COVID-19 vaccination and its associated factors. The review reported that females, including homemakers, lacked literacy regarding COVID-19 vaccination compared to males [ 29 ]. This finding suggests that homemakers may have less knowledge and information about COVID-19 vaccination, which could contribute to their vaccination hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Tamara et al investigated the refusal of the COVID-19 vaccination and its associated factors. The review reported that females, including homemakers, lacked literacy regarding COVID-19 vaccination compared to males [ 29 ]. This finding suggests that homemakers may have less knowledge and information about COVID-19 vaccination, which could contribute to their vaccination hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in 2023 and based on 24 articles estimated the average COVID-19 vaccine hesitancy rate to be 12% [14]. According to this systematic review, individuals with a high socioeconomic status, history of previous vaccination, and medical background had a lower rate of COVID-19 vaccination refusal.…”
Section: Introductionmentioning
confidence: 95%